PENGARUH SISTEM PENJUALAN E-COMMERCE, PENGGUNAAN SISTEM INFORMASI AKUNTANSI, DAN PERILAKU KEUANGAN TERHADAP KINERJA KEUANGAN UMKM DI KOTA MADIUN - Tunnisa, Dilla Ayu; Widodo, Nova Maulud; Rahayu, Nika Esti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The success of MSMEs in their business process can be seen from how good the financial performance of the business is. This study aims to analyze the influence of E-commerce Sales System, the Use of Financial Information Systems and Financial Behavior on Financial Performance in Micro, Small and Medium Enterprises (MSMEs) in Madiun City. This research method uses a quantitative method with primary data obtained through survey techniques. The sample from this study is MSME actors in Madiun City. The data analysis techniques used were multiple linear regression analysis, normality test, multicollinearity test, heteroscedasticity test, and t test. The tool used in this study is the Statistical Package for the Social Science (SPSS) Version 22 software. The results of this study show that the variables of the E-commerce sales system have a positive and significant effect on financial performance, the variables of the use of accounting information systems do not have a significant influence on financial performance, and the variables of financial behavior have a positive and significant influence on financial performance. The author suggests that MSMEs in Madiun City use an E-commerce sales system and good financial behavior so that it can help improve their financial performance.